An integrative transformative service framework to improve engagement in a social service ecosystem: the case of He Waka Tapu. Issue 4 (10th July 2017) - Hepi, Maria; Foote, Jeff; Finsterwalder, Jörg, Moana-o-Hinerangi; Carswell, Sue; Baker, Virginia
Abstract : Purpose: This study aims to understand the engagement between an indigenous social service provider and marginalised clients deemed "hard-to-reach" to gain an insight into how to improve the client's engagement and well-being through transformative value co-creation. Design/methodology/approach: The exploratory study's findings draw on primary data employing a qualitative research approach through document analysis and in-depth interviews with clients, social workers and stakeholders of the focal social service provider in New Zealand. Findings: The findings indicate that there are inhibitors and enablers of value or well-being co-creation. The lack of client resources and a mismatch between client and social worker are primary barriers. Other actors as well as cultural practices are identified as enablers of well-being improvement. Research limitations/implications: This research reports on a single social service provider and its clients. These findings may not be readily transferrable to other contexts. Practical implications: Findings indicate that social service providers require a heightened awareness of the inhibitors and enablers of social service co-creation. Social implications: Both the integrative framework and the findings provide a sound critique of the prevailing policy discourse surrounding the stigmatisation of members of society deemed "hard-to-reach" and the usefulness of such an approach when aiming at resolving social issues. Originality/value: This is the first exploratory study that reports on the engagement between a social service provider and its clients in a dedicated Māori (indigenous) context by employing an integrative research approach combining transformative service research, activity theory and engagement theory.